If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3z + -7z = 28 Combine like terms: 3z + -7z = -4z -4z = 28 Solving -4z = 28 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Divide each side by '-4'. z = -7 Simplifying z = -7
| 4x+12=2x+30 | | w^2-24= | | 8x-6=24 | | -2x^2-4+8x=0 | | 10=x/3+x/7 | | 10=10(y-5)+5y | | -207=1+4(-8v+4) | | 7x-12=3x-16 | | (3a-2b)(3a+3b)=0 | | 6(1-3A)=132 | | 6x-4+2x=28 | | 6(4a+2)=94 | | 6b+10=-14 | | 170-2x=25x+23 | | 3(m+1)+2m=88 | | 2x^2+8y=5x+20 | | 5(8-x)=3x | | -5(6n-4)+2n= | | 3p-3+7p=4p+6 | | 60x=32x | | 60x=26x | | 0.01x+4.74=2.05x-3.42 | | 5*(-2t-3)-(5-(5t+2))=1 | | X^2+8x-xy-8y=0 | | 1/2(4x)=-20 | | 10=15x | | 4x^2-30x+14=0 | | 5x^2-2x=x^2-10x | | 18h*483=462*21h | | 6(3N-1)=-96 | | 3y+5y=64y | | 7y+7=6r+12 |